Perineurium-like sheath derived from long-term surviving mesenchymal stem cells confers nerve protection to the injured spinal cord. (April 2018) - Ma, Yuan-Huan; Zeng, Xiang; Qiu, Xue-Cheng; Wei, Qing-Shuai; Che, Ming-Tian; Ding, Ying; Liu, Zhou; Wu, Guo-Hui; Sun, Jia-Hui; Pang, Mao; Rong, Li-Min; Liu, Bin; et al.
Abstract: The functional multipotency enables mesenchymal stem cells (MSCs) promising translational potentials in treating spinal cord injury (SCI). Yet the fate of MSCs grafted into the injured spinal cord has not been fully elucidated even in preclinical studies, rendering concerns of their safety and genuine efficacy. Here we used a rat spinal cord transection model to evaluate the cell fate of allograft bone marrow derived MSCs. With the application of immunosuppressant, donor cells, delivered by biocompatible scaffold, survived up to 8 weeks post-grafting. Discernible tubes formed by MSCs were observed beginning 2 weeks after transplantation and they dominated the morphological features of implanted MSCs at 8 weeks post-grafting. The results of immunocytochemistry and transmission electron microscopy displayed the formation of perineurium-like sheath by donor cells, which, in a manner comparable to the perineurium in peripheral nerve, enwrapped host myelins and axons. The MSC-derived perineurium-like sheath secreted a group of trophic factors and permissive extracellular matrix, and served as a physical and chemical barrier to insulate the inner nerve fibers from ambient oxidative insults by the secretion of soluble antioxidant, superoxide dismutase-3 (SOD3). As a result, many intact regenerating axons were preserved in the injury/graft site following the forming of perineurium-like sheath. A parallel study utilizing a good manufacturing practice (GMP) grade human umbilical cord-derived MSCs or allogenic MSCs in an acute contusive/compressive SCI model exhibited a similar perineurium-like sheath formed by surviving donor cells in rat spinal cord at 3 weeks post-grafting. The present study for the first time provides an unambiguous morphological evidence of perineurium-like sheath formed by transplanted MSCs and a novel therapeutic mechanism of MSCs in treating SCI.